Improving knowledge for targeting interventions: willingness of individuals to participate and calculation of environment indices - Rubiano, J.; García, J. (CGIAR Challenge Program on Water and Food, 2009)
We present a method for the calculation of individuals’ willingness to participate (IWP) and an institutional environment index (IEI). A description of the approach, data and procedures is presented using as a case study of data for municipalities in Bolivia. We use these procedures as examples of how these two indicators can be estimated using secondary data. The method can be easily applied to countries with relatively good socio-economic secondary data at municipal level to produce continental or sub-continental pictures of these two key factors. The purpose of developing these two indicators was to provide better information for targeting interventions as identified by the implementation of Extrapolation Domain Analysis (EDA).